A Patient with Suspect Chronic Myeloid Leukemia: A Case Report - Dharmawaiswari, Anak Agung Ayu Ratih; Tedja, I Gusti Ayu Wiradari; Prianggandanni, Made Ayu Vita; Dharmawati, I Gusti Agung Ayu; Bekti, Heri Setiyo (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Chronic myeloid leukemia (CML) is a type of cancer that starts in the blood-forming cells of the bone marrow. In contrast to other types of leukemia, chronic myeloid leukemia (CML) progresses slowly. This report covers a 52-year-old male patient who came to the emergency room at Wangaya Regional Hospital with weakness, nausea, and pallor. His weight had drastically decreased over the last few months. The clinical condition of the patient was that both eyes appeared anemic, and the abdominal examination revealed hepatomegaly. Complete blood count examination results showed the following results: leukocytes 222.73x103/µl, hemoglobin 7.3 g/dL, platelets 679x103/µl, neutrophil 87.5%, neutrophil/lymphocyte ratio 16.66%. The results of peripheral blood smear analysis showed that hyperleukocytosis, with the maturation stage of myelocyte cells with a percentage of myeloblasts 6%, promyelocytes 7%, myelocytes 6%, metamyelocytes 8%, neutrophils 10%, neutrophil segments 60%, other cells 3%. These examination results suggest chronic myeloid leukemia. However, to confirm the diagnosis, the BCR-ABL fusion protein must be expressed, which can be used to identify the presence or absence of the Philadelphia chromosome in patients diagnosed with chronic myeloid leukemia (CML).